2009
DOI: 10.1038/jhh.2009.28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of angiotensin receptor blockade in combination with hydrochlorothiazide 25 mg in 2121 patients with stage 1–2 hypertension

Abstract: The antihypertensive effects of telmisartan 80 mg versus valsartan 160 mg, both combined with hydrochlorothiazide (HCTZ) 25 mg, were assessed in a pooled analysis from two large trials with identical study designs in patients with stage 1-2 hypertension. The trials were double-blind with a 4:4:1 randomization scheme to compare once-daily telmisartan 80 mg and HCTZ 25 mg versus once-daily valsartan 160 mg and HCTZ 25 mg versus once-daily placebo on reductions in clinic blood pressure (BP). The primary end point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…When a smoothness index was used to evaluate the 24-hour antihypertensive efficacy of several agents, telmisartan 80 mg had a significantly higher smoothness index than the ARBs losartan and valsartan and the ACE inhibitor, ramipril, and was comparable with amlodipine [87]. Telmisartan effectively reduces BP when used alone [32,34,88,89] or in combination with HCTZ [86,90-94] or amlodipine [37,95,96]. Telmisartan/HCTZ has demonstrated superiority over losartan/HCTZ in patients with essential hypertension in terms of 24-hour ambulatory BP, including a BP-lowering effect during the last 6 hours of the dosing interval [92,97,98].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a smoothness index was used to evaluate the 24-hour antihypertensive efficacy of several agents, telmisartan 80 mg had a significantly higher smoothness index than the ARBs losartan and valsartan and the ACE inhibitor, ramipril, and was comparable with amlodipine [87]. Telmisartan effectively reduces BP when used alone [32,34,88,89] or in combination with HCTZ [86,90-94] or amlodipine [37,95,96]. Telmisartan/HCTZ has demonstrated superiority over losartan/HCTZ in patients with essential hypertension in terms of 24-hour ambulatory BP, including a BP-lowering effect during the last 6 hours of the dosing interval [92,97,98].…”
Section: Introductionmentioning
confidence: 99%
“…In the Study of Micardis ® on Obese/Overweight Type-II diabetics with Hypertension (SMOOTH ® ), telmisartan/HCTZ demonstrated significantly greater reductions in mean ambulatory BP over the entire 24-hour dosing interval and during the last 6 hours compared with valsartan/HCTZ [93]. In two large, placebo-controlled trials, telmisartan/HCTZ also demonstrated antihypertensive superiority over valsartan/HCTZ in patients with stages 1 and 2 hypertension [86,94]. …”
Section: Introductionmentioning
confidence: 99%
“…A pooled analysis of the two studies showed that the significant difference in BP reduction in favor of T80/H25 was maintained, regardless of age, sex, or race of the patients 44. In patients with essential hypertension, the T/H SPC was significantly more efficacious than the losartan/HCTZ SPC in reducing BP during the last 6 hours of the dosing interval, as well as in reducing 24-hour ambulatory BP after 6 weeks of treatment 45–47.…”
Section: Comparison With Other Spcsmentioning
confidence: 96%
“…Two independent and identically designed trials were previously conducted to evaluate the benefits and safety of two single-pill combination (SPC) therapies: telmisartan 80 mg plus HCTZ 25 mg (T80/H25) and valsartan 160 mg plus HCTZ 25 mg (V160/H25) in patients with stages 1 and 2 hypertension [15, 16]. A pooled analysis of these two studies provided support for the use of ARBs with this higher 25 mg dose of thiazide diuretic; furthermore, the analysis demonstrated that T80/H25 resulted in greater reductions in clinic BP than V160/H25 [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In our pooled analysis of T80/H25 versus V160/H25, a substantial proportion of patients participating had stage (or grade) 2 hypertension [17]. The aim of the present analysis was to evaluate the efficacy and tolerability of both combination antihypertensive treatments in those patients who had moderate-to-severe hypertension, specifically defined as systolic BP (SBP) ≥ 160 mm Hg at baseline.…”
Section: Introductionmentioning
confidence: 99%